If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 39.7 + b + 30.01 = 165.288 Reorder the terms: 39.7 + 30.01 + b = 165.288 Combine like terms: 39.7 + 30.01 = 69.71 69.71 + b = 165.288 Solving 69.71 + b = 165.288 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-69.71' to each side of the equation. 69.71 + -69.71 + b = 165.288 + -69.71 Combine like terms: 69.71 + -69.71 = 0.00 0.00 + b = 165.288 + -69.71 b = 165.288 + -69.71 Combine like terms: 165.288 + -69.71 = 95.578 b = 95.578 Simplifying b = 95.578
| 24+c=3c-18 | | (4a^2x+2ax^2+a^2x^2)=0 | | 35-7q=-5 | | 7-5m=-5-2m | | V-7V=-6V-1 | | 5x-7=5-x | | 4p-(p-15)=6(10-p)+4p | | 5(5(4z-19)+z-4)-2=24 | | 12+c=5c-5 | | (3x^2+9x-12)=0 | | -2(2n+5)=8 | | 12+6z-12=5z+1 | | 88c-11-10=86c+11 | | 4x-2=5x+28-x | | 16+7t=8t+16 | | 58=(9/5)c+32 | | -2x+4=7 | | -11n+4=-7n-8 | | 7(y-3)=3y-37 | | 8x=10-5 | | -3d=5.7 | | (2x-6)+(2x-6)+3+3=54 | | -5+10=13X-4-12x | | x-(5-3c)=7x+4 | | 6x-8=7x+1 | | -1.8d=0.54 | | (6x^2+3x+5)=0 | | 4+x-2x=28 | | .5(t-6)=1 | | 10x+8-9x=10 | | 2d=2.4 | | (42abc-12a^2b^2+3abc)=0 |